Biosynthesis of silver nanoparticles using Acinetobacter calcoaceticus ІМV V-7241 cell-free supernatant - Laziuka, Yuliya; Kharchenko, Yevgen; Skrotska, Oksana (My University, 2020)
Currently, the biological synthesis of nanoparticles and their properties and application in the fields of medicine and the environment is an important area of nanotechnology. Synthesis of nanoparticles using chemical and physical methods has several disadvantages. These drawbacks include the use of toxic solvents, the formation of dangerous by-products and high energy consumption. Therefore, it is important to obtain nanoparticles in a biogenic way, in particular by microorganisms. The mechanisms of biogenic synthesis of nanoparticles have not been fully studied. There are reports on the role of surface active agents (surfactants) in this process. Therefore, the producer of surfactants Acinetobacter calcoaceticus ІМВ В-7241 (which was isolated from the oil contaminated environment) was selected for the study.
Keywords: наночастинки срібла; бактерії; біосинтез; silver nanoparticles; bacteria; biosynthesis; Acinetobacter calcoaceticus ІМВ В-7241; кафедра біотехнології і мікробіології